2020
DOI: 10.1136/bmjgh-2019-002128
|View full text |Cite
|
Sign up to set email alerts
|

Prioritising gender, equity, and human rights in a GRADE-based framework to inform future research on self care for sexual and reproductive health and rights

Abstract: IntroductionIn January 2019, the WHO reviewed evidence to develop global recommendations on self-care interventions for sexual and reproductive health and rights (SRHR). Identification of research gaps is part of the WHO guidelines development process, but reliable methods to do so are currently lacking with gender, equity and human rights (GER) infrequently prioritised.MethodsWe expanded a prior framework based on Grading of Evidence, Assessment, Development and Evaluation (GRADE) to include GER. The revised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“… 36 While some studies have investigated diagnostic accuracy of self-sampling for reproductive tract infections in pregnancy, evidence on their benefits, harms and effective linkages with health systems is currently lacking. 37 Lastly, we identified self-care studies on insecticide-treated nets for malaria, mostly from the sub-Saharan Africa region. However there was little research on other low-cost strategies amenable to a self-care approach (indoor residual spraying and insect repellents), or from other malaria-endemic regions such as Asia and Latin America.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 36 While some studies have investigated diagnostic accuracy of self-sampling for reproductive tract infections in pregnancy, evidence on their benefits, harms and effective linkages with health systems is currently lacking. 37 Lastly, we identified self-care studies on insecticide-treated nets for malaria, mostly from the sub-Saharan Africa region. However there was little research on other low-cost strategies amenable to a self-care approach (indoor residual spraying and insect repellents), or from other malaria-endemic regions such as Asia and Latin America.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, self-collection of vaginal samples for reproductive tract infections is an emerging alternative to clinic-based sampling 36. While some studies have investigated diagnostic accuracy of self-sampling for reproductive tract infections in pregnancy, evidence on their benefits, harms and effective linkages with health systems is currently lacking 37. Lastly, we identified self-care studies on insecticide-treated nets for malaria, mostly from the sub-Saharan Africa region.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this article is the first describing and evaluating the process to develop a mission-driven Research Agenda undertaken by a large center within a state public health department. We adapted processes utilized in the development of prior plans and research agendas to suit the needs and capacity of our organization 6,10–19. Research questions were requested from nearly 230 external stakeholders, including research and subject matter experts throughout the state, to ensure the agenda reflected research gaps identified by those actively conducting research or working in relevant areas; a long-standing advisory body; and internal staff.…”
Section: Discussionmentioning
confidence: 99%
“…The development process for this Research Agenda included components common to the development of previous NYSDOH plans 6,10 and other public health research agendas [11][12][13][14][15][16][17][18][19] but was adaptive and did not follow a specified predetermined framework. The process began in early 2021 with the formation of an internal Research Agenda Committee.…”
Section: Methodsmentioning
confidence: 99%
“…It must come with better evidence on what strategies work to enhance the capacities of individuals and communities to access quality self-care interventions. A structure to support further research that includes stakeholder values and identification of core gender, equity and human rights standards and principles can strengthen the evidence base [ 7 ]. Strong partnerships, collaborative approaches and political will become increasingly important alongside evidence-based instruments and tools to assess the starting point and map the desired directions for policy change.…”
mentioning
confidence: 99%